PENGARUH KERAGAMAN PRODUK DAN LOKASI TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN PADA TOKO JAYA BARU SITUBONDO - fayumi, Makki; Hamdun, Edy Kusnadi; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing is an important element in a company to determine whether a business is successful or not, for that the company must apply the understanding of marketing with a large amount in order to survive. The purpose of this study is to determine the effect of product diversity on consumer satisfaction. the population in this study is all Consumers who dated to The jaya baru Store. the method of random sampling (simple probability sampling) tampa pays attention to stara in the population in this study conducted. In taking this saampel using a presentation level of 10%. Data analysis and hypothesis testing in the study using the Structural-partial Least squere (PLS-SEM) equation model. The results of the hypothesis test directly affect using the SMART PLS 3.0 application, show that product diversity Jaya Baru a significant positive effect on consumer satisfaction. Location Jaya Baru a significant positive effect on consumersatisfaction. Product diversity Jaya Baru a significant positive effect on consumer loyalty. Location Jaya Baru a significant positive effect on consumer loyalty. Consumer satisfaction Jaya Baru a significant positive effect on consumer loyalty. Product diversity to consumer loyalty through consumer satisfaction Jaya Baru a positive but insignificant effect.Location to Consumer loyalty through customer satisfaction Jaya Baru a significant positive effect.